Penerapan Good Farming Practices Sapi Potong di Distrik Masni, Kabupaten Manokwari: Implementation of Good Farming Practices for Beef Cattle in Masni District, Manokwari Regency - Anwarudin, Oeng; Pardosi, Hotmauli Febriana; Paya, Asri Takke (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2024)
Background: Efforts to develop beef cattle breeders have been implemented with various efforts such as community extension and empowerment, capital assistance, farmer institutional development, and artificial insemination programs. These activities should have an impact on the application of good beef cattle farming. Objectives: The study aimed to determine the extent of the application of Good Farming Practices (GFP) and what factors determine the application of Good Farming Practices. Methods: This research was conducted in Masni District, Manokwari Regency, West Papua Province. The series of research activities were carried out from February to July 2024. The number of samples was 50 respondents with Proportionate cluster random sampling technique. This research is quantitative research with data analysis methods, namely descriptive statistical analysis and multiple regression. Results: The results showed that the implementation of GFP of farmers was in the medium category. The condition of GFP implementation in Masni District is that most farmers have access to transportation, feed and clean water, and are free from clinical anthrax disease.  However, it is necessary to increase the application of GFP in the amount of feeding, mating, housing, recording and animal welfare. Factors influencing the application of GFP are institutional support which includes farmer institutions such as farmer groups and farmer group associations, government, and the Agricultural Extension Center. Conclusion: Farmers have not implemented beef cattle GFP optimally. Improving the implementation of GFP can be done through strengthening institutional support which includes the support of farmer institutions, government and Agricultural Extension Center support.